How to Purify and Experiment with Dye Adsorption using Carbon: Step-by-Step Procedure from Carbon Conversion from Agricultural Biomass to Concentration Measurement Using UV Vis Spectroscopy - Asep Bayu Dani Nandiyanto; Meli Fiandini; Risti Ragadhita; Muhammad Aziz (Indonesian Journal of Science and Technology, 2023)
This paper contains guidelines and provides a basic understanding of how to do experiments in dye adsorption using carbon. This paper presents a step-by-step experimental procedure from carbon preparation (as biochar) from agricultural waste to concentration measurement using UV-Vis Spectroscopy. We used agricultural waste as a model due to its high cellulose and organic content, making it easily converted into carbon. This paper can be used as a guide for researchers and students in the fabrication of carbon from agricultural waste biomass easily and inexpensively for its application as an adsorbent in the batch adsorption process. This paper also supports the current issues in Sustainable Development Goals (SDGs).